ECOLOGICAL EDUCATION IS AN IMPORTANT FACTOR FOR SOCIETY AND ITS DEVELOPMENT (Scientific journal of the Fergana State University, 2023)
The article analyzes the teaching of the subjects "Ecology and nature protection", "Ecology", "People's pedagogy" taught in higher pedagogical education courses, problems in this regard, technologies for the development of mechanisms of ecological education in students studying in these courses. The experimental program developed for improvement, the development of environmental education of students according to it, the assessment criteria, the conducted experimental tests and the conclusions in this regard are covered in detail.